2018
DOI: 10.1021/acs.energyfuels.8b02448
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Artifacts in the Methylation Process of Sulfur Compounds in Petroleum

Abstract: Methylation of sulfides and thiophenes into methyl sulfonium salts for electrospray ionization (ESI) mass spectrometry analysis has been a widely used approach for molecular characterization of sulfur-containing compounds in fossil fuels. In this study, we found a series of artifacts in the methylation products of crude oils, which could lead to incorrect assignment of sulfur compounds, severe ionization suppression of S1 species with a high double bond equivalent value, and O x S x species with low abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To provide context, S -methylation analyzed via ESI is known to have compromised repeatability and reproducibility due to the molecular selectivity of methylation, the stability of the sulfonium cation, 40 and potential artifact formation. 41 In contrast, the reproducibility of APPI for detecting sulfur-containing compounds was evaluated by Son et al in 2020. 42 They reported a relative standard deviation (RSD) of less than 1% for S1 class compounds detected at high abundances (up to 45%).…”
Section: Resultsmentioning
confidence: 99%
“…To provide context, S -methylation analyzed via ESI is known to have compromised repeatability and reproducibility due to the molecular selectivity of methylation, the stability of the sulfonium cation, 40 and potential artifact formation. 41 In contrast, the reproducibility of APPI for detecting sulfur-containing compounds was evaluated by Son et al in 2020. 42 They reported a relative standard deviation (RSD) of less than 1% for S1 class compounds detected at high abundances (up to 45%).…”
Section: Resultsmentioning
confidence: 99%
“…The methylation/demethylation method has been successfully used for the separation of sulfides and thiophenes from the petroleum fraction in total or separately. The separation performance of the method was excellent; however, a long reaction time of the methylation step has limited it wide use in the laboratory as a routine method. Using AgSbF 6 , the methylation/demethylation method will be more useful for the sulfur compound separation.…”
Section: Resultsmentioning
confidence: 99%
“…S-Methylation of sulfur compounds has been widely used for molecular characterization of sulfur compounds in fossil fuels by ESI FT-ICR MS. However, Wang et al 173 found a series of artifacts in the methylation products of crude oils, which could lead to incorrect assignment of sulfur compounds. The terminal products from the Friedel-Craft methylation of toluene and its methyl homologues were identified as 1,1,2,3,4,5,6heptamethylbenzenonium, which showed high abundance in the positive-ion ESI mass spectrum.…”
Section: Approaches and Applications Formentioning
confidence: 99%